2023
DOI: 10.1186/s41606-023-00083-3
|View full text |Cite
|
Sign up to set email alerts
|

From good sleep to health and to quality of life – a path analysis of determinants of sleep quality of working adults in Abu Dhabi

Abstract: Background Sleep quality has significant impacts on many aspects of quality of life. Therefore, identifying the association of sleep quality with that quality of life domains could lead to deeper insights for social policymakers and professionals to enhance their understanding of the lives of Abu Dhabi working adults. This research focuses on sleep quality among working people in Abu Dhabi. The direct and indirect associations of sleep quality with various quality-of-life domains such as income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…This study used data from the fourth cycle of the Abu Dhabi Quality of Life survey (QoL-4), which comprehensively incorporated subjective indicators drawn from prominent sources such as the OECD's Better Life Index, the World Happiness Report, the Gallup Global Well-being Survey, and the European Quality of Life Survey [58,59,60] . Additionally, QoL-4 introduced a diverse array of dimensions and factors thought to influence the well-being of Abu Dhabi residents, encompassing dimensions ranging from housing, household income, employment, and to health, education, safety, and social connections.…”
Section: Instrument and Surveymentioning
confidence: 99%
“…This study used data from the fourth cycle of the Abu Dhabi Quality of Life survey (QoL-4), which comprehensively incorporated subjective indicators drawn from prominent sources such as the OECD's Better Life Index, the World Happiness Report, the Gallup Global Well-being Survey, and the European Quality of Life Survey [58,59,60] . Additionally, QoL-4 introduced a diverse array of dimensions and factors thought to influence the well-being of Abu Dhabi residents, encompassing dimensions ranging from housing, household income, employment, and to health, education, safety, and social connections.…”
Section: Instrument and Surveymentioning
confidence: 99%
“…Sleep is an essential physiological process for the survival of human beings. Having good sleep quality is crucial since it greatly affects various aspects in relation to quality of life 3 ) . Chronic exposure to poor sleep quality is related to depression, anxiety, and other health problems 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It is a cause for concern among the general public and academic organizations, as more effort is needed to persuade students to limit their use of electronic devices before bedtime to maintain good sleep hygiene and quality. Improved sleep quality is associated with improved physical and psychological well-being [3], [15]. Studies done in Morocco and Qatar on university students reported that good habits are strongly linked to good overall sleep quality [16], [17].…”
Section: Introductionmentioning
confidence: 99%